Spatial Analysis of Landslide Potential in Agricultural Areas of Wadaslintang Catchment Area, Central Java Province Indonesia - Gina Isna Nafisa; Chandra Setyawan; Ngadisih Ngadisih; Sahid Susanto; Nur Ainun Harlin Jennie Pulungan (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2025)
Landslides have occurred in several tropical regions of Indonesia and caused many losses in both upstream and downstream areas. This study aims to identify landslide prone areas in the Wadaslintang catchment area, Central Java Province Indonesia. Nine parameters were used to analyze landslide potential such as land use, land slope, rainfall, constituent rocks, soil type, soil permeability, population density, drainage density and runoff coefficient. Each parameter has five possibility scores ​​(1 to 5) determined based on certain criteria. The value of each parameter was presented in a raster map with 15 meters of resolution and analyzed in ArcGIS 10.8. The level of landslide susceptibility was classified into five categories. The relationship between landslides and the triggered factor was analyzed using Frequency Ratio (FR). The result showed that the parameters with the highest FR values were land use, land slope, rainfall, and soil permeability, indicating a strong influence on landslides. Very high vulnerability areas were found in mixed farmland and settlements especially on steep slopes. Area with moderate and low categories of landslide vulnerability covers the largest area of the study site with an occupied area of 98.54 km2 (51.04% of the total area) and 57.91 km2 (29.99% of the total area), respectively. While the others i.e., areas with the very low, high and very high categories, occupy around of 3.74 km2 (1.94% of the total area), 30.94 km2 (16.02% of the total area), and 1.93 km2 (1% of the total area) respectively. Validation results indicated that landslides mostly occurred in areas with medium and high categories of landslide vulnerability.